RESPONDING TO GLOBAL INJUSTICE: ON THE RIGHT OF RESISTANCE. Issue 1 (2015) - Caney, Simon
Abstract: In the debates surrounding global justice, the overwhelming focus has been on the duties that fall to the affluent and powerful, and the emphasis has been on their duties to comply with various principles of justice. In this essay, I examine what those who bear the brunt of global injustice are entitled to do to secure their own entitlements and those of others. In particular, I defend an account of what I term the "right of resistance against global injustice." To do so I advance several methodological and substantive claims. On the methodological level: I argue that in deriving and defining this right of resistance we can (a) learn from the normative accounts developed to analyze war, humanitarian intervention, civil disobedience, revolution and anti colonialism. However, (b) the right to resist global injustice raises some distinct problems; and, thus, the normative principles that should inform any right of resistance against global injustice are not reducible to those that govern the appropriate kinds of response to other kinds of injustice. Turning now to the substantive component, I propose an account of resisting global injustice that specifies (i) who may engage in resistance, (ii) what would constitute a just cause for engaging in resistance, (iii) against whom those engaging in resistance may impose burdens, (iv) what methods resistors can employ, and (v) in what circumstances resistance is permissible.